Defining evidence-based marketing strategies for wine producers and wine tourist destinations : is the total antioxidant index approach valuable? - Droli, Maurizio (Array, 2019)
The Total Antioxidant Index (TAA-I) can be viewed as a wine added value, for which consumers are willing to pay, and as a determinant in developing successful differentiated marketing strategies. This interdisciplinary study aims to harness potentials existing in an evidence-based wine TAA-I and territorial data on wine production. According to the Resource Based Theory (RBT), only above-average performances identify valuable resources. By applying the theory, data on regional areas planted with vines as well as a seminal study ranking thirteen selected Italian wines based on their TAA-I have been analyzed. Wine growing vocation represents a valuable resource only in six out of twenty Italian regions. Eleven vine areas of origin can be assumed as being important, especially in Northern and Central Italy. The TAA-I positions achieved by selected wines are far from being expressed, and thus promoted, by adopting labels based on production traditions. The 1997 sample database adopted by this study needs to be updated with a more recent one and expanded in further researches. Thus, researches of evidencebased marketing, thus hidden and objective quality attributes of wine, are needed and urgent but still in their infancy. Results obtained by this study allow decision makers to set-up a RBT-rooted benchmark system connecting biomedical studies, economic and marketing studies.